2008
DOI: 10.1111/j.1742-481x.2007.00408.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with bone marrow‐derived stromal cells accelerates wound healing in diabetic rats

Abstract: Bone marrow stem cells participate in tissue repair processes and may have a role in wound healing. Diabetes is characterised by delayed and poor wound healing. We investigated the potential of bone marrow-derived mesenchymal stromal cells (BMSCs) to promote healing of fascial wounds in diabetic rats. After manifestation of streptozotocin (STZ)-induced diabetic state for 5 weeks in male adult Sprague-Dawley rats, healing of fascial wounds was severely compromised. Compromised wound healing in diabetic rats was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
113
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(120 citation statements)
references
References 44 publications
(56 reference statements)
5
113
0
Order By: Relevance
“…Furthermore, in our experiment, quality of wound healing (in terms of epithelization, neovascularization and collagen deposition characteristics) on 28 th day post surgery was found to be better in stem cell and CM groups than control groups. Kwon et al [5] reported that allogenic stem cell treatment resulted in thicker, denser and well arranged collagen deposition in diabetic wound healing in rabbits though, did not correlated it with conditioned media (no study available regarding treatment with stem cell conditioned media). No significant difference in stem cell treatment and CM treatment may be due to treatment with these two in small intervals (about 7 day interval).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, in our experiment, quality of wound healing (in terms of epithelization, neovascularization and collagen deposition characteristics) on 28 th day post surgery was found to be better in stem cell and CM groups than control groups. Kwon et al [5] reported that allogenic stem cell treatment resulted in thicker, denser and well arranged collagen deposition in diabetic wound healing in rabbits though, did not correlated it with conditioned media (no study available regarding treatment with stem cell conditioned media). No significant difference in stem cell treatment and CM treatment may be due to treatment with these two in small intervals (about 7 day interval).…”
Section: Discussionmentioning
confidence: 99%
“…Group I, II and III were non-diabetic while group IV, V and VI were diabetic with six animals in each group (Table 1). Group II and V received stem cells (2x10 5 per dose) in culture media and group III and VI received conditioned media (1ml dose) while group I and IV were kept as respective controls given only stem cell culture media (1 ml dose). Stem cells and its conditioned media were injected at the periphery of wounds.…”
Section: Wound Creation and Animal Experimentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, cell therapy with bone marrow mesenchymal stem cells (MSCs) has been trialed to treat chronic wounds in diabetics [5][6][7] . The main functional characteristics of MSCs are their immunomodulatory ability, capacity for self-renewal, and differentiation into mesodermal tissues, such as bone cells 8 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, direct injection of cultured BMMSC into the wound area in normal diabetic mice promoted wound healing through release of proangiogenic factors upon differentiation (39). ; In streptozocin (STX)-induced diabetic rats, BMMSC double-system injections through the tail vein and local injection at the wound site augmented growth factors such as EGF, VEGF, PDGF-BB markedly and TGF-β and KGF moderately (40). BMMSC induce potent differentiation and proliferation under low oxygen tension with cell morphological and cell cycle changes and differentiation capacity towards bone and fat (42).…”
mentioning
confidence: 99%